New e-learning course to tackle complex challenges of managing dryland forests and agrosilvopastoral systems - Carleton, Elliot; Louhaichi, Mounir; Flintan, Fiona (CGIAR System Organization, 2023)
a blog about the e-learning course, "Transforming Dryland Forests and Agrosilvopastoral Systems" introduced by The Committee on Forestry Working Group on Dryland Forests and Agrosilvopastoral Systems (COFO-WG) and the Food and Agriculture Organization (FAO). the course is designed to address challenges faced by these ecosystems covering 41% of the global land area. Supporting approximately two billion people globally, these areas play a crucial role in poverty alleviation, food security, and livelihoods. However, degradation, deforestation, and climate change threaten their integrity. The e-learning course, developed in collaboration with 15 partner organizations, including ILRI and ICARDA, aims to bridge knowledge gaps, build capacity, and promote sustainable practices. Mounir Louhaichi, from ICARDA, played a key role in its development, ensuring diverse content for optimal student engagement. The course, part of the Livestock and Climate initiative, aligns with the International Year of Rangelands and Pastoralists' goals, fostering understanding and training in sustainable land management practices on rangelands. The interdisciplinary approach and incorporation of action research make it a valuable tool for capacity-building and transformative solutions in managing dryland ecosystems.